Simulating Pump–Probe Photoelectron and Absorption Spectroscopy on the Attosecond Timescale with Time‐Dependent Density Functional Theory. Issue 7 (20th March 2013) - De Giovannini, Umberto; Brunetto, Gustavo; Castro, Alberto; Walkenhorst, Jessica; Rubio, Angel
Abstract Molecular absorption and photoelectron spectra can be efficiently predicted with real‐time time‐dependent density functional theory. We show herein how these techniques can be easily extended to study time‐resolved pump–probe experiments, in which a system response (absorption or electron emission) to a probe pulse is measured in an excited state. This simulation tool helps with the interpretation of fast‐evolving attosecond time‐resolved spectroscopic experiments, in which electronic motion must be followed at its natural timescale. We show how the extra degrees of freedom (pump‐pulse duration, intensity, frequency, and time delay), which are absent in a conventional steady‐state experiment, provide additional information about electronic structure and dynamics that improve characterization of a system. As an extension of this approach, time‐dependent 2D spectroscopy can also be simulated, in principle, for large‐scale structures and extended systems.